PROSES PERAKITAN DAN PENGUJIAN KUBIKEL SM6 VACUUM CIRCUIT BREAKER 20 kV DI PT. GALLEON CAHAYA INVESTAMA - Redaksi Tim Jurnal (Energi & Kelistrikan, 2018)
At PT. Galleon Cahaya Investama which in this case much needed electrical appliance to be used in distribution network that is one tool of cubicles before marketed at other company. Cubiclesis a connecting device, divider and disconnecting load doing testing. In this cubicle insulation testing,cubicle is already in pairs and have connected with The transformer after that just done insulation testing with mega ohm meter, because cubicle is already 5 with the transformer then the insulation resistance value will be reduced because of the existing transformer windings in it. In testing leakage current PMT component is still in good condition, seen from test results that is still Below 300 μA, and in the test of isolation resistance, also in good condition, looking from the results that have been tested still shows the value above the standard isolation resistance. With visual inspection by looking at the results of work with the eyes and tools, namely see the shape, rust and placement of components that have been right.